Operating the Railway Traffic Control System - Pepevnik, Anton; Kolenc, Jurij (Promet - Traffic&Transportation, 2003)
In agreement with the adopted traffic policy and with thedevelopment strategy of the Republic of Slovenia the SlovenianRailways will also integrate into the development strategic objectivesof the European railways. The perspective of improvementlies mainly in following the development of the Europeansystem.The technology and organization of the railway traffic systeminclude all the technological and organizational elementsand processes that take part in the realization of the system objectives.The notion system from the formal mathematical perspectiveindicates a roundup whole which is usually complex oreven very complex. The technology and organization of workinclude a multitude of means and procedures in order to carryout the basic activity which presents a roundup whole, the processof passenger and freight transport in the traffic system.Fast progress of microelectronics and computer science inthe last decade has brought a new generation of electronic signal-safety devices.All the changes of the last years that have been introducedin the railway technology raised the attractiveness of the railwaytransport. It is competitive with other forms of transport, so thatthe Slovenian Railways have to follow the development of technologyand gradually modernize its line network.